Biochemical screening of intellectually disabled and healthy children in Punjab, Pakistan: differences in liver function test and lipid profiles. (26th May 2020) - Wasim, Muhammad; Khan, Haq Nawaz; Ayesha, Hina; Awan, Fazli Rabbi
Abstract : Objectives: Inborn errors of metabolism (IEMs) are rare genetic disorders. Generally, IEMs are untreatable; however, some IEMs causing intellectual disability are potentially treatable if diagnosed earlier. In this study, levels of some clinically important biochemical parameters in intellectually disabled children suspected for IEMs were tested to see their association with intellectual disability, which could be helpful in preliminary screening. Methods: This comparative cross-sectional observational study was carried out from 2014 to 2017. Blood samples from 800 boys and girls (aged 4–24 years) were collected, of which 391 were healthy (IQ >90) and 409 were intellectually disabled (IQ <70) children with unknown cause. Clinically important (Liver and kidney enzymes etc.) biochemical parameters were analyzed in sera samples using commercial kits on semi-automated clinical chemistry analyzer. Results: Serum analysis showed the levels of ALP ( p  < 0.00001), ASAT ( p  = 0.001), ALAT ( p  = 0.016), albumin ( p  < 0.001), uric acid ( p  < 0.001), cholesterol ( p  < 0.001), triglycerides ( p  < 0.001), and hemoglobin ( p  = 0.005) were significantly different between healthy and intellectually disabled children. Conclusion: Changes in the liver function test and lipid profile parameters were significantly different in children with intellectual disability; however, it requires further detailed analysis for complete characterization of these diseases.